Aloin Regulates Matrix Metabolism and Apoptosis in Human Nucleus Pulposus Cells via the TAK1/NF-κB/NLRP3 Signaling Pathway - Taiqiu Chen; Pengfei Li; Jincheng Qiu; Wenjun Hu; Shaoguang Li; Huihong Shi; Xianjian Qiu; Dongsheng Huang; Wenjie Gao; Anjing Liang (Stem Cells International)
Intervertebral disc degeneration (IDD) is a degenerative disease that is characterized by decreased matrix synthesis and extra degradation, nucleus pulposus cells (NPCs) apoptosis, and infiltration of inflammatory factors. Aloin, a colored compound from aloe plants, has been shown to be effective against skeletal degenerative diseases, but it is unclear whether it is protective against IDD. Herein, we investigated the role of aloin in NPCs. In our study, the upregulation of proinflammatory factors, apoptosis, and unbalanced matrix metabolism were observed in degenerative NP tissues. We found that aloin had a curative effect on extracellular matrix metabolism and apoptosis in TNF-alpha- (TNF-α-) treated NPCs by inhibiting oxidative stress and the proinflammatory factor expression. Further investigation revealed that aloin treatment suppressed the TAK1/NF-κB pathway. Moreover, the expression level of the NLPR3 inflammasome was downregulated after aloin treatment in TNF-α-treated NPCs. In summary, our results demonstrated that aloin treatment can reverse TNF-α-induced unbalanced matrix metabolism and apoptosis of NPCs via the TAK1/NF-κB/NLRP3 axis. This study supports that aloin can be a promising therapeutic agent for IDD.